Dynamic Buckling of Embedded Laminated Nanocomposite Plates Based on Sinusoidal Shear Deformation Theory - Mohammd Sharif Zarei; Mohammad Hadi Hajmohammad; Ali Nouri (Journal of Applied and Computational Mechanics, 2016)
In this study, the dynamic buckling of the embedded laminated nanocomposite plates is investigated. The plates are reinforced with the single-walled carbon nanotubes (SWCNTs), and the Mori-Tanaka model is applied to obtain the equivalent material properties of them. Based on the sinusoidal shear deformation theory (SSDT), the motion equations are derived using the energy method and Hamilton's principle. The Navier’s method is used in conjunction with the Bolotin's method for obtaining the dynamic instability region (DIR) of the structure. The effects of different parameters such as the volume percentage of SWCNTs, the number and orientation angle of the layers, the elastic medium, and the geometrical parameters of the plates are shown on DIR of the structure. Results indicate that by increasing the volume percentage of SWCNTs the resonance frequency increases, and DIR shifts to right. Moreover, it is found that the present results are in good agreement with the previous researches.